1994
DOI: 10.1017/s0031182000068335
|View full text |Cite
|
Sign up to set email alerts
|

A nematode FMRFamide-like peptide, SDPNFLRFamide (PF1), relaxes the dorsal muscle strip preparation ofAscaris suum

Abstract: PF1 (SDPNFLRFamide) is a FMRFamide-like peptide extracted from the free-living nematode Panagrellus redivivus. Here we show that this peptide causes a hyperpolarization of somatic muscle cells of the parasitic nematode Ascaris suum and a relaxation of the somatic muscle strip preparation. We have assessed whether or not the relaxation of Ascaris dorsal muscle strip by PF1 is due to (i) inhibition of the release of the excitatory neuromuscular junction transmitter acetylcholine (ACh), (ii) potentiation of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 16 publications
7
51
0
Order By: Relevance
“…The six peptides with Cterminal -PGVLRFamide (AF3, AF4, AF10, AF13, AF14, and AF20) all increased muscle tension, as did AF1, AF5, AF8, AF9, and AF17 (the effects of AF8 have also been reported by Maule et al 1994). AF11, the peptide with C-terminal -PNFLRFamide, relaxed muscle, similar to the effects of the Panagrellus peptide SDPNFLRFamide (Bowman, Geary & Thompson, 1990;Franks et al 1994;Bowman et al 1995). Muscle was also relaxed by AF6 and AF19.…”
Section: Neuropeptidessupporting
confidence: 52%
“…The six peptides with Cterminal -PGVLRFamide (AF3, AF4, AF10, AF13, AF14, and AF20) all increased muscle tension, as did AF1, AF5, AF8, AF9, and AF17 (the effects of AF8 have also been reported by Maule et al 1994). AF11, the peptide with C-terminal -PNFLRFamide, relaxed muscle, similar to the effects of the Panagrellus peptide SDPNFLRFamide (Bowman, Geary & Thompson, 1990;Franks et al 1994;Bowman et al 1995). Muscle was also relaxed by AF6 and AF19.…”
Section: Neuropeptidessupporting
confidence: 52%
“…The lack of' eflect of the nicotin1ic receptor aintagonists tubocurarine and mecamylaminic show's thcat the cffect of' acetylcholine is mcdiatcd by ainon-nicotiniic receptor (Colquhoun vet al 199 1 PF1 is an FMRFamide peptide that depresses the contractility of Ascaris somatic muscle and produces a non-Cl--mediated hyperpolarization (Franks, Holden-dye, Williams, Pang & Walker, 1994;Bowman, Winterrowd, Friedman, Thompson, Klein, Davis, Maule, Blair & Geary, 1995). PF1 also antagonizes the postsynaptic potentials produced by stimulating motoneurones (Franks et al 1994). We tested the effects of PF1 on Ibeat in three preparations at concentrations between 0 5 and 3 /LM and observed a depressent effect on 'beat Figure 5D shows the depressant effect of 1 /LM PF1 on the voltage-dependent bag current following acetylcholine and Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The effect of PF1 was also shown to be mediated via NO. Franks et al (1994) have reported an antagonistic effect of PF1 on muscle EPSPs evoked by electrical stimulation of motoneurones and suggested that the action of PF1 was a presynaptic inhibition of acetycholine release. In this study, we have observed a direct antagonism of the effects of acctylcholine in the isolated bag preparation.…”
Section: Effects Of Pf1mentioning
confidence: 99%
“…In contrast to the rapid inhibitory response of PF4 on A. suum somatic muscle cells, PF1's inhibitory effect is slow and also independent of the inhibitory action of GABA (Franks et al 1994). In addition to their postsynaptic effect to inhibit muscle contraction, both PF1 and PF2 act presynaptically on motoneuron terminals to inhibit ejps, and this effect is independent of any effect of bath-applied acetylcholine-induced muscle cell depolarization.…”
Section: Nematodesmentioning
confidence: 92%